Economic Stability in Islamic View : Approach to Controlling Inflation - Anggara, Windu; Shawab, Nabil; Abd. Majid, M. Shabri; Harahap, Isnaini (Publisher Cv. Inara, 2023)
Economic stability is the main goal in the Islamic view, in which economic concepts based on ethical values ??and social justice are prioritized. One of the problems faced in achieving economic stability is inflation which can cause imbalance and instability in the economy. Therefore, this paper discusses the approach put forward from an Islamic perspective to control inflation and achieve sustainable economic stability, through: 1) implementation of a sharia-based monetary system, which prohibits usury (interest) and excessive speculation, 2) currency management, 3) equity in income distribution, 4) encouraging investment in the productive sector and economic infrastructure, and 5) economic supervision and regulation. The narrative of this research is told in accordance with the requirements of the formulation being addressed. It is a descriptive qualitative study with a literature study technique. The findings of this study demonstrate that, from an Islamic perspective, attempts to maintain economic stability and manage inflation are not just commercial endeavors but also an essential component of worship for achieving social welfare and justice. By implementing these approaches, it is hoped that the economy in the Islamic view can achieve sustainable stability and provide long-term benefits for society as a whole.